6-Gingerol protects cardiocytes H9c2 against hypoxia-induced injury by suppressing BNIP3 expression. Issue 1 (4th December 2019) - Ren, Qi; Zhao, Shaojun; Ren, Changjie
Abstract: Background: Cardiomyocytes loss is the predominant pathogenic characteristic in the hypoxia-induced injury. Meanwhile, it has been corroborated that Bcl-2 E1B 19-KDa interacting protein 3 (BNIP3) provokes apoptosis and autophagy. For moderating cardiomyocytes loss, we initially probed the cyto-protection effects of 6-Gingerol (6 G), meanwhile, its potential mechanisms associated with BNIP3 were elucidated in our studies. Methods: We pretreated cardiomyocytes H9c2 cells with 6 G at different concentrations (0–100 μM) before exposure to hypoxia. Thereafter, the cell viability, lactate dehydrogenase (LDH), apoptosis and protein expression were respectively assessed using cell counting kit-8 and methyl thiazolyl tetrazolium (MTT) assay, LDH assay kit, Annexin V-fluorescein isothiocyannate/propidium iodide (Annexin V-FITC/PI) apoptosis detection kit and Western blotting analysis. In addition, we also analyzed BNIP3 level after treatment. Moreover, we enforced the exogenous overexpression of BNIP3 and then evaluated the cell viability, apoptosis, and protein level again. Results: In our present work, we observed that the cell viability was promoted by 6 G in the hypoxia-induced H9c2 cells in a dose-dependent manner. Moreover, hypoxia-induced LDH release, apoptosis and autophagy were inhibited by 6 G pretreatment through promoting phosphorylation of PI3K, AKT and mTOR. Remarkably, accumulation of BNIP3 protein was significantly reduced by 6 G in hypoxia-induced H9c2 cells. Mechanistically, 6 G initiated the phosphorylated expression of PI3K, AKT and mTOR by down-regulating BNIP3 with reducing cardiomyocytes apoptosis and autophagy. Conclusion: Hypoxia-induced cardiomyocytes injury was ameliorated by 6 G through suppressing BNIP3 expression with triggering PI3K/AKT/mTOR signalling pathway.